2009
DOI: 10.1007/s00259-009-1145-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of full-dose FDG PET/CT for axillary lymph node staging in breast cancer patients

Abstract: FDG PET/CT cannot replace invasive approaches for axillary staging but may extend the indication for SLNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
1
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 38 publications
4
124
1
8
Order By: Relevance
“…Garami et al [10] found that 18 IQR interquartile range, ALN axillary lymph node, NS not significant, DCIS ductal carcinoma in situ, ER estrogen, PR progesterone choose between SLNB and ALND. This triage has the potential to reduce the number of ALN dissections applied [13]. In a study performed by Reddy and Srivastava [14], PET/CT was compared with SLNB to evaluate axillary lymph node involvement in 37 patients with T1T2N0 breast carcinoma.…”
Section: Detecting Aln Metastasesmentioning
confidence: 99%
“…Garami et al [10] found that 18 IQR interquartile range, ALN axillary lymph node, NS not significant, DCIS ductal carcinoma in situ, ER estrogen, PR progesterone choose between SLNB and ALND. This triage has the potential to reduce the number of ALN dissections applied [13]. In a study performed by Reddy and Srivastava [14], PET/CT was compared with SLNB to evaluate axillary lymph node involvement in 37 patients with T1T2N0 breast carcinoma.…”
Section: Detecting Aln Metastasesmentioning
confidence: 99%
“…In the study of Heusner et al, the primary tumour was FDG PET positive in 87% of cases [3]. However, 39% of patients had clinical stage T1.…”
Section: Primary Tumour Assessmentmentioning
confidence: 92%
“…PET/CT allows diagnosis of infraclavicular, supraclavicular and internal mammary node involvement and can depict occult distant metastases. Preliminary findings from Heusner and colleagues suggest that the information provided by FDG PET/ CT might be useful in extending the indication of SLNB to patients with tumours larger than 2-3 cm [3]. The role of PET in assessing response to neoadjuvant chemotherapy is also growing, and a baseline PET is necessary for that purpose.…”
Section: Assessing Distant Metastasesmentioning
confidence: 99%
“…Several groups have demonstrated that, in most cases, FDG-PET or PET/CT has a low sensitivity (range 24-82 %) but a high specificity (range 80-100 %) and high positive predictive value (PPV) of more than 80 % [24][25][26][27][28][29][30][31][32][33]. In a review of 472 patients examined using FDG-PET/CT, the pooled sensitivity was relatively low (60 %) but the pooled specificity was very high (97 %) [34].…”
Section: Axillary Lymph Node Stagingmentioning
confidence: 99%